2020
DOI: 10.1038/s41598-020-58717-w
|View full text |Cite|
|
Sign up to set email alerts
|

World Trade Center-Cardiorespiratory and Vascular Dysfunction: Assessing the Phenotype and Metabolome of a Murine Particulate Matter Exposure Model

Abstract: Vascular changes occur early in the development of obstructive airways disease. However, the vascular remodeling and dysfunction due to World trade center-particulate Matter (Wtc-pM) exposure are not well described and are therefore the focus of this investigation. C57Bl/6 female mice oropharyngeally aspirated 200 µg of Wtc-pM 53 or phosphate-buffered saline (PBS) (controls). 24-hours (24-hrs) and 1-Month (1-M) after exposure, echocardiography, micro-positron emission tomography(µ-pet), collagen quantification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…44REAP-S scores can range from 15-39, and higher quantities represent dietary quality characterized by optimal intake of fruits, vegetables, and whole grains and decreased intake of sugary foods, processed meats, and fried foods. Scores were categorized into low-dietary (15)(16)(17)(18)(19), moderatedietary (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and high-dietary (30-39) quality, Table 3. Additionally, REAP-S questions were assessed as distinct food categories.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…44REAP-S scores can range from 15-39, and higher quantities represent dietary quality characterized by optimal intake of fruits, vegetables, and whole grains and decreased intake of sugary foods, processed meats, and fried foods. Scores were categorized into low-dietary (15)(16)(17)(18)(19), moderatedietary (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and high-dietary (30-39) quality, Table 3. Additionally, REAP-S questions were assessed as distinct food categories.…”
Section: Methodsmentioning
confidence: 99%
“…Speci cally, RAGE de cient WTC-PM exposed mice were protected against WTC-OAD. (25)(26)(27) Dietary and endogenous AGEs can impact signaling pathways such those in in ammatory diseases. (28) Despite evidence that diet and obesity are risks, studies have suggested obesity may have a protective effect on survival and lung function in COPD.…”
mentioning
confidence: 99%
“…REAP-S scores can range from 15-39, and higher quantities represent dietary quality characterized by optimal intake of fruits, vegetables, and whole grains and decreased intake of sugary foods, processed meats, and fried foods. Scores were categorized into low-dietary [15][16][17][18][19], moderatedietary [16,[20][21][22][23][24][25][26][27][28], and high-dietary [29][30][31][32][33][34][35][36][37][38] quality, Table 3. Additionally, REAP-S questions were assessed as distinct food categories.…”
Section: Nutritional Assessmentmentioning
confidence: 99%
“…Our in vitro and in vivo models identified that the receptor for AGE (RAGE) is associated with lung dysfunction after WTC-particulate matter (WTC-PM) exposure. Specifically, RAGE deficient WTC-PM exposed mice were protected against WTC-OAD [ [24][25][26]. Dietary and endogenous AGEs can impact signaling pathways such as those in inflammatory diseases [27].…”
mentioning
confidence: 99%
“…Speci cally, RAGE de cient WTC-PM exposed mice were protected against WTC-OAD. (24)(25)(26) Dietary and endogenous AGEs can impact signaling pathways such those in in ammatory diseases. (27) Despite evidence that diet and obesity are risks, studies have suggested obesity may have a protective effect on survival and lung function in COPD.…”
Section: Introductionmentioning
confidence: 99%